Regulation of renal organic anion and cation transporters by in cisplatin induced kidney injury - Ulu, Ramazan; Dogukan, Ayhan; Tuzcu, Mehmet; Gencoglu, Hasan; Ulas, Mustafa; Ilhan, Necip; Şahin, Kazım (Pergamon-Elsevier Science Ltd, 2012)
In previous studies, we have demonstrated the biological activity of thymoquinone (TQ), an active compound extracted from the Nigella sativa plant, against cisplatin-induced neurotoxicity. Recenty, it was observed that there is an inherent lack in regulation of renal organic anion and cation transporters in cisplatin-induced nephrotoxicity. Here, we report, for the first time, the effect of TQ on alterations in the renal expression of organic anion transporters (OATs) and organic cation transporters (OCTs), as well as multidrug resistance-associated proteins (MRPs) in rats treated with cisplatin. Twenty-eight 8-week-old male Wistar rats were divided into four groups of control, TQ treated (10 mg/kg b.w. in drinking water for 5 days), cisplatin (7 mg/kg b.w., i.p.) and TQ and cisplatin combination treatment. Cisplatin-induced malondialdehyde (MDA) and 8-isoprostane increase was found to be markedly reduced in rats treated with TQ. In cisplatin only treated rats, the induced renal injury increased protein levels of the efflux transporters MRP2 and MRP4 while expression of OAT1, OAT3, OM and OCT2 was reduced. In combination TQ- and cisplatin-treated rats, expression of MRP2 and MRP4 proteins was decreased in the kidneys. Conversely, TQ treatment increased levels of OCT1, OCT2, OAT1 and OAT3 and decreased levels of 8-isoprostane and MDA levels in cisplatin-treated rats. In conclusion, the present study shows that the TQ synergizes with its nephroprotective effect against cisplatin-induced acute kidney injury in rats. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Cisplatin; Kidney; OATs/OCTs; MRPs; Thymoquinone